Integrasi Chatbot Berbasis NLP pada Sistem Layanan Akademik Universitas - Tarigan, Heskyel Pranata (Jurnal Komputer, 2024)
The advancement of digital technology has driven transformation in the delivery of information services in higher education institutions. One innovation that is being increasingly adopted is the use of Natural Language Processing (NLP)-based chatbots in academic service systems. This chatbot enables natural conversation-based interactions between users and systems, facilitating students in accessing information quickly and efficiently. This paper discusses the basic concepts, benefits, system architecture, and challenges faced in integrating NLP-based chatbots into academic service systems. By adopting this approach, universities can enhance service quality, reduce administrative burdens, and promote the digitalization of academic processes in a comprehensive manner.